The role of plant secondary metabolites in shaping regional and local plant community assembly. (1st April 2021) - Endara, María‐José; Soule, Abrianna J.; Forrister, Dale L.; Dexter, Kyle G.; Pennington, R. Toby; Nicholls, James A.; Loiseau, Oriane; Kursar, Thomas A.; Coley, Phyllis D.
Abstract: The outstanding diversity of Amazonian forests is predicted to be the result of several processes. While tree lineages have dispersed repeatedly across the Amazon, interactions between plants and insects may be the principal mechanism structuring the communities at local scales. Using metabolomic and phylogenetic approaches, we investigated the patterns of historical assembly of plant communities across the Amazon based on the Neotropical genus of trees Inga (Leguminosae) at four, widely separated sites. Our results show a low degree of phylogenetic structure and a mixing of chemotypes across the whole Amazon basin, suggesting that although biogeography may play a role, the metacommunity for any local community in the Amazon is the entire basin. Yet, local communities are assembled by ecological processes, with the suite of Inga at a given site more divergent in chemical defences than expected by chance Synthesis . To our knowledge, this is the first study to present metabolomic data for nearly 100 species in a diverse Neotropical plant clade across the whole Amazonia. Our results demonstrate a role for plant–herbivore interactions in shaping the clade's community assembly at a local scale, and suggest that the high alpha diversity in Amazonian tree communities must be due in part to the interactions of diverse tree lineages with their natural enemies providing a high number of niche dimensions. Abstract : Using metabolomic and phylogenetic approaches, we show that species of the Neotropical tree genus Inga, have dispersed freely across the Amazon. However, the subset of Inga species that coexist in any given forest community differ dramatically from each other in their chemical defences. Thus, interactions between plants and herbivores are a major factor shaping community composition in tropical rain forests. Resumen: La increíble diversidad de los bosques Amazónicos se cree es el resultado de varios procesos. Aunque los linajes de Inga se han dispersado repetidamente a lo largo de la Amazonía, las interacciones entre plantas e insectos podrían ser el mecanismo más importante en el ensamblaje de comunidades a escala local. Usando métodos metabolómicos y filogenéticos, investigamos los patrones históricos de ensamblaje de comunidades de plantas a lo largo de la Amazonía basándonos en el género neotropical de árboles Inga (Leguminosae) en cuatro sitios, ampliamente separados. Nuestros resultados demuestran un grado de estructura filogenética y una mezcla de chemotipos a lo largo de la Amazonía, sugiriendo que aunque la biogeografía juegue un rol, la metacomunidad para cualquier comunidad regional en la Amazonía es toda la cuenca Amazónica. Comunidades locales son ensambladas por procesos ecológicos, donde todas las especies de Inga coexistiendo en un mismo sitio son más divergentes en defensas químicas que al azar. Síntesis . Este es el primer estudio que presenta datos metabolómicos para casi 100 especies de árboles pertenecientes a un grupo Neotropical diverso a lo largo de su rango de distribución. Nuestros resultados demuestran un rol para las interacciones entre plantas y herbívoros en el ensamblaje de la comunidad de este clado a escala local, y sugiere que la alta diversidad alfa en las comunidades de árboles Amazónicos puede deberse en parte a las interacciones de grupos de árboles diversos con sus enemigos naturales.